2007
DOI: 10.1111/j.1750-3841.2006.00222.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Food Systems of Lactobacillus rhamnosus R011 Microentrapped in Whey Protein Gel Particles

Abstract: The aim of this study was to investigate the effect of whey protein isolate (WPI) gel microentrapment on the viability of Lactobacillus rhamnosus R011 during the production and storage of biscuits, frozen cranberry juice, and vegetable juice. Viability of microentrapped (ME) cells was compared to free cells freeze-dried in a milk-based protective solution as well as in a WPI-based solution (ungelled). During the production of biscuits and their storage for 2 wk at 23 degrees C, the highest stability was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 34 publications
0
49
0
7
Order By: Relevance
“…Studies in vivo and in vitro have shown that the nature of food harboring probiotics affected their viability (Ainsley Reid et al 2007). In this respect, the nature of the whey proteins was found to affect the entrapment of the probiotic Lb.…”
Section: Whey Protein Products Usedmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in vivo and in vitro have shown that the nature of food harboring probiotics affected their viability (Ainsley Reid et al 2007). In this respect, the nature of the whey proteins was found to affect the entrapment of the probiotic Lb.…”
Section: Whey Protein Products Usedmentioning
confidence: 99%
“…The viability of Lb. rhamnosus R011 microencapsulated in whey protein beads during the production and storage of biscuits, frozen cranberry juice, and vegetable juice was compared to free cells freeze-dried in the milk-based protective solution and in a denatured whey protein isolate-based solution (ungelled) enriched with lactose and sucrose (Ainsley Reid et al 2007). During the production and storage of biscuits for 2 weeks at 23°C, cells micro-entrapped in whey protein isolate gel particles showed the minimum drop in cell counts (from 1.3×10 7 to <10 3 cfu.g −1 ).…”
Section: Post-preparation Behavior Of Probiotic Loaded Wp Micro-beadsmentioning
confidence: 99%
“…A utilização da microencapsulação também pode aumentar a resistência das bactérias no decorrer do trato digestório, visto que esse meio possui elevada acidez, além da presença de enzimas e da bile, possibilitando que as bactérias cheguem ao intestino em quantidade, com condições de sobrevivência e de colonização (CHAMPAGNE;FUSTIER, 2007;FAVARO-TRINDADE et al, 2008).…”
Section: Microencapsulação De Probióticosunclassified
“…As micropartículas são produzidas por uma mistura contendo o ingrediente ativo (ou recheio) e o agente encapsulante na forma de gotículas. Essa mistura é pulverizada por um atomizador ou bico aspersor e entra em uma câmara, na qual o ar circula a baixa temperatura (CHAMPAGNE;FUSTIER, 2007). O esquema do método, bem como o desenho do equipamento estão apresentados nas Figura 1.…”
Section: Técnicas Empregadas Na Microencapsulação De Probióticosunclassified
See 1 more Smart Citation